2011
DOI: 10.1002/qre.1264
|View full text |Cite
|
Sign up to set email alerts
|

Economically Optimum Design of a Synthetic Chart

Abstract: This paper proposes an economic model for the synthetic chart. The synthetic chart is an integration of the trueX¯ chart and the CRL chart. A simplified algorithm to obtain the optimal parameters of the synthetic chart which minimizes the expected cost function is introduced. Numerical examples based on different values of input parameters are given, and sensitivity analyses of the parameters are performed. The input parameters which have a significant impact on the cost and choice of optimal parameters of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Yeong et al proposed the first economic model for the S1 chart in which they formulated an algorithm to find the optimal values of the chart's design parameters, which minimize the net sum of all costs involved, so that the chart can be operated at an economically optimal level by using the approximation of the cost function in Chung . Recently, Yeong et al further showed the economic efficiency of the S1 trueX¯ chart as compared with that of the ordinary trueX¯ chart.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yeong et al proposed the first economic model for the S1 chart in which they formulated an algorithm to find the optimal values of the chart's design parameters, which minimize the net sum of all costs involved, so that the chart can be operated at an economically optimal level by using the approximation of the cost function in Chung . Recently, Yeong et al further showed the economic efficiency of the S1 trueX¯ chart as compared with that of the ordinary trueX¯ chart.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They used various tools which can maximize their individual benefits from a holistic point of view of total quality. Yeong et al [20] proposed an economic model for the synthetic chart that is an integration of the X chart and the CRL chart. Numerical examples, based on different values of input parameters were given, and sensitivity analyses of the parameters were performed.…”
Section: -P2mentioning
confidence: 99%
“…The notion of selecting chart parameters to minimise cost over time has intuitive appeal, especially when the economic consequences of the design are significant. Therefore, the research community (see Xie, Tang, and Goh 2001;Zhang, Xie, and Goh 2005;Yeong et al 2012;Park 2013) has allocated part of its efforts to the development and improvement of optimisation models for economic design of control charts.…”
Section: Introductionmentioning
confidence: 99%